The role of shariah authority in enhancing the Islamic financial system in Malaysia and Indonesia - Ro’fah Setyowati; Mohammad Azam Hussain; Ruzian Markom; Mohd Izzat Amsyar Mohd Arif (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Shariah Authority plays an essential role in confirming that the products and services of Islamic finance companies comply with Shariah principles. The Shariah Advisory Board and the National Shariah Council are the highest authorities for determining Islamic law for Islamic financial transactions in Malaysia and Indonesia, respectively -the Shariah Advisory Board of Malaysia reports to the Central Bank of Malaysia. At the same time, the National Shariah Council of Indonesia was part of the Indonesian Ulema Council, a non-governmental organisation. The latter is thus part of the regulatory framework and complements the financial system. As the two councils are different in nature, the rulings have different implications for the community. This article aims to analyse the status of the Shariah Authority in terms of the establishment and procedures for deriving the rulings. The research is qualitative and uses content analysis by looking at the legislation that governs these institutions. The research findings show that the Shariah authority in both countries has the same function in the industry but differs in terms of the creation of the rulings, the procedures and the attachment to the Islamic financial institutions, courts and arbitrators. In conclusion, the article proposes several improvements by the relevant agencies to strengthen the framework of the Shariah authority in Malaysia and Indonesia, leading to accountable administration to the industry, the community and the state.